Indonesian Muslim Scholars’ Conceptions on the Method of Thematic Interpretation of the Qur’an - Izza Rohman (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2009)
This study deals with Indonesian Muslim scholars’ discussions on the method of thematic interpretation of the Qur’an during the period of 20 years, from the mid-1980s to the mid-2000s. It shows that, in Indonesian discourses on thematic method of Qur’an interpretation, three issues are recurrently dealt with: what kind of themes is most desirable, what principles should be underlined, and in what way the method of thematic interpretation should be applied. While some scholars argue that it would be better if the theme selected is closely related to the real problems facing the society like poverty and backwardness, some others do not privilege a certain kind of theme over the others. Regardless of the theme or the term to be discussed, however, two principles are commonly and recurrently highlighted with regard to the application of thematic method. The first is the importance of treating the Qur’an is on its own terms as a unity. The second is the importance of paying close attention to the chronology of the Qur’an revelation. As for the issue of how the method of thematic interpretation should be applied, this study shows that there are free important models of thematic interpretation introduced in Indonesia: the one that was popularized by Quraish Shihab, the one that is introduced by Dawam Rahardjo, and the one that was named thematic-chronological method by Taufik Adan Amal and Syamsu Rizal Panggabean while discussing a contextual approach to the Qur’an.